Model PDP Balaghah Al-Wadihah Berasaskan PAK21 - Yuslina Mohamed; Wan Moharani Mohammad; Muhammad Marwan Ismail; Mohamed Haji Ibrahim; Zulkipli Md Isa; Sulaiman Ismail; Nurhasma Muhd. Saad (Universiti Sains Islam Malaysia, 2024)
Papers In MALAY Language Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia